Keadilan Gender Dalam Keluarga Perspektif Amina Wadud - Muhammad Fadhil; Munawwir Ramadhan (Fakultas Syariah dan Hukum Universitas Islam Negeri Sumatera Utara, 2026)
This study examines the concept of gender justice in Muslim families through the perspective of Amina Wadud, particularly in the reinterpretation of the concept of qiwamah contained in QS. An-Nisa verse 34. The concept of qiwamah is traditionally often interpreted as the legitimacy of superiority and absolute leadership of men over women in the family structure, which creates a gender hierarchy and places women in a subordinate position. This study uses a normative juridical method with a hermeneutic approach to analyze Amina Wadud's thoughts sourced from her works, especially